Care for Mechanics: Development of Motorcycle Workbench Based on ADDIE Model to Reduce Musculoskeletal Disorders - Junara, Riska Ade; Estriyanto, Yuyun; Towip (JST (Jurnal Sains dan Teknologi), 2023)
In a developing country like Indonesia, where the majority of the population is working in the informal sectors, there is a need for ergonomic tool intervention, which is low cost, and easy in terms of manufacturability with locally available materials.  The rapid growth of motorcycle sales in Indonesia has stimulated the growth of motorcycle repair workshops. However, some of the non-authorized repair workshops ignore the occupational safety of the mechanics. This study aims to develop a motorcycle workbench as a tool for maintenance work to reduce musculoskeletal disorders (MSDs). The present study used Research and Development (R&D) with the ADDIE model combined with an ergonomic approach. The research subjects were 4 mechanics from one private workshop. Data was collected using interview, observation, and questionnaire techniques. The MSDs data was analyzed using Nordic Musculoskeletal Questionnaire (NMQ). The ergonomic risk factors were analyzed using Rapid Upper Limb Assessment (RULA) and Ovako Work Posture Analysis System (OWAS).  The result showed an improvement in the work posture of mechanics. The MSDs complaint decreased based on NMQ Score. Furthermore, the RULA score and OWAS score also decreased. Thus, the development of the motorcycle workbench succeeded in reducing the MSDs complaint and improving mechanics’ occupational safety.